Non-front-fanged colubroid ("colubrid") snakebites: Three cases of local envenoming by the mangrove or ringed cat-eyed snake (Boiga dendrophila; Colubridae, Colubrinae), the Western beaked snake (Rhamphiophis oxyrhynchus; Lamprophiidae, Psammophinae) and the rain forest cat-eyed snake (Leptodeira frenata; Dipsadidae). (April 2014) - Weinstein, S. A.; Griffin, R.; Ismail, A. K.
Abstract: Context. Non-front-fanged colubroid snakes (NFFC; formerly and artificially taxonomically assembled as "colubrids") comprise the majority of extant ophidian species. Although the medical risks of bites by a handful of species have been documented, the majority of these snakes have oral products (Duvernoy's secretions, or venoms) with unknown biomedical properties/unverified functions and their potential for causing harm in humans is unknown. Case details. Described are three cases of local envenoming from NFFC bites inflicted respectively by the mangrove or ringed cat-eyed snake ( Boiga dendrophila, Colubridae), the Western beaked snake ( Rhamphiophis oxyrhynchus, Lamprophiidae) and the rain forest cat-eyed snake ( Leptodeira frenata, Dipsadidae). The effects ranged from mild pain, edema and erythema to severe pain, progressive edema, and blistering with slowly resolving arthralgia; there were no systemic effects. Discussion. Although these three taxa occasionally inflict bites with mild to moderate local effects, there is no current evidence of systemic involvement. Two of these cases were reported to one of the authors for medical evaluation, and although verified, thus constitute reliably reported cases, but low-quality evidence. Type-1 local hypersensitivity may contribute to some cases, but most local effects observed or reported in these three cases were consistent with the effects of venom/oral product components.